The Long Shadow of the Past: Early-Life Disease Environment and Later-Life Mortality - Hamid Noghanibehambari; Jason M. Fletcher (Institute of Labor Economics (IZA), 2023)
A recently growing literature evaluates the influence of early-life conditions on life-cycle health and mortality. This paper extends this literature by estimating the associations between birth-state infant mortality rates experienced during early-life (as a proxy for general disease environment, health-care access, and nutrition) and life-cycle mortality rates. Using the universe of death records in the US over the years 1979-2020 and implementing two-way fixed effect models, we find that a 10 percent rise in birth-state infant mortality rate is associated with about 0.23 percent higher age-specific mortality rate. These correlations are more concentrated in ages past 50, suggesting delayed effects of early-life exposures. Moreover, we find substantially larger correlations among nonwhites, suggesting that the observed racial disparities in mortality can partly be explained by disparities in early-life conditions. Further, we provide empirical evidence to argue that reductions in education, income, and socioeconomic scores are likely mechanism channels.
Keywords: I18; J13; N31; N32; 330; mortality; infant mortality; early-life exposures